Sperm epimutation biomarkers of obesity and pathologies following DDT induced epigenetic transgenerational inheritance of disease. Issue 2 (27th May 2019) - King, Stephanie E; McBirney, Margaux; Beck, Daniel; Sadler-Riggleman, Ingrid; Nilsson, Eric; Skinner, Michael K
Abstract: Dichlorodiphenyltrichloroethane (DDT) has previously been shown to promote the epigenetic transgenerational inheritance of adult onset disease in rats. The current study investigated the potential that sperm epimutation biomarkers can be used to identify ancestral induced transgenerational obesity and associated pathologies. Gestating F0 generational female rats were transiently exposed to DDT during fetal gonadal sex determination, and the incidence of adult-onset pathologies was assessed in the subsequent F1, F2, and F3 generations. In addition, sperm differential DNA methylation regions (DMRs) that were associated with specific pathologies in the transgenerational F3 generation males were investigated. There was an increase of testis disease and early-onset puberty in the F2 generation DDT lineage males. The F3 generation males and females had significant increases in the incidence of obesity and multiple disease. The F3 generation DDT males also had significant increases in testis disease, prostate disease, and late onset puberty. The F3 generation DDT females had increases in ovarian and kidney disease. Epigenetic alterations of the germline are required for the transgenerational inheritance of pathology. Therefore, the F3 generation sperm was collected to examine DMRs for the ancestrally exposed DDT male population. Unique sets of DMRs were associated with late onset puberty, prostate disease, kidney disease, testis disease, obesity, and multiple disease pathologies. Gene associations with the DMR were also identified. The epigenetic DMR signatures identified for these pathologies provide potential biomarkers for transgenerationally inherited disease susceptibility.